2019
DOI: 10.24143/2073-5529-2019-1-112-121
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Fish Muscle of Small Rivers of the Yaroslavl Region

Abstract: The article presents the study results of the chemical composition of Cyprinidae and Percidae skeletal muscles from the Sot', Vopsha and Kast' rivers in the territory of the Yaroslavsky State Nature Reserve. The fish were ascertained for sex, stage of gonad maturity, and age. The total amount of water, dry matter, total lipids, protein, minerals, and nitrogen-free extractives (NFE) were determined in their muscle tissues. The study revealed significant differences in the content of final metabolic products in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…In the muscles of juvenile specimens, there was seen low content of fat compared with mature bream (Table 3, 5, 6). Earlier, research revealed that in bodies of fish, regardless of their living location, the amount of metabolic products differed insignificantly (Nargis, 2006;Yousaf et al, 2011;Payuta et al, 2019a;Payuta & Flerova, 2019). Reduced content of protein and increased amount of carbohydrates in the muscles of males were determined in marine and freshwater fish, including Cyprinidae, in a number of studies (Medford & Mackay, 1978;Nargis, 2006;Payuta et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the muscles of juvenile specimens, there was seen low content of fat compared with mature bream (Table 3, 5, 6). Earlier, research revealed that in bodies of fish, regardless of their living location, the amount of metabolic products differed insignificantly (Nargis, 2006;Yousaf et al, 2011;Payuta et al, 2019a;Payuta & Flerova, 2019). Reduced content of protein and increased amount of carbohydrates in the muscles of males were determined in marine and freshwater fish, including Cyprinidae, in a number of studies (Medford & Mackay, 1978;Nargis, 2006;Payuta et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, research revealed that in bodies of fish, regardless of their living location, the amount of metabolic products differed insignificantly (Nargis, 2006;Yousaf et al, 2011;Payuta et al, 2019a;Payuta & Flerova, 2019). Reduced content of protein and increased amount of carbohydrates in the muscles of males were determined in marine and freshwater fish, including Cyprinidae, in a number of studies (Medford & Mackay, 1978;Nargis, 2006;Payuta et al, 2019a). The studies of chemical composition in the bodies of Cyprinidae and Pleuronectidae found higher content of fat in the bodies of mature fish compared with immature specimens (Rijnsdorp & Ibelings, 1989;Payuta et al, 2019a;Payuta & Flerova, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations